Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1249/01.mss.0000210202.33070.55
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pacing Strategies during the Cycle Phase of an Ironman Triathlon

Abstract: These data show evidence that a nonlinear dynamic pacing strategy is used by well-trained triathletes throughout various segments and conditions of the Ironman cycle phase. Moreover, an increased variation in torque and speed was found in the headwind versus the tailwind condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 34 publications
(1 reference statement)
1
54
0
8
Order By: Relevance
“…2,7,[20][21][22] Furthermore, few studies have considered the pacing of multiple-lap events. Abbiss et al 15 reported a significant decrease in power output, cadence, and speed during the 3-lap cycling phase of an Ironman triathlon, demonstrating a positive pacing strategy. During the shorter cycling phase of an Olympic triathlon, a significant decrease in power output and velocity has also been observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,7,[20][21][22] Furthermore, few studies have considered the pacing of multiple-lap events. Abbiss et al 15 reported a significant decrease in power output, cadence, and speed during the 3-lap cycling phase of an Ironman triathlon, demonstrating a positive pacing strategy. During the shorter cycling phase of an Olympic triathlon, a significant decrease in power output and velocity has also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords: off-road cycling, multiple laps, terrain, teleoanticipation, self-paced exercise variation in power output as mean power decreased as the cycle phase progressed, whereas in the Ironman distance, Abbiss et al 15 reported that the high degree of oscillation in power output for each lap was maintained even though performance time increased for each lap. The maintenance of high intralap variation was thought to be evidence of a nonlinear dynamic pacing strategy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…power output relative to a given effort) rather than fixed power output. This approach is helpful for the comparison of athletes when it is done at the power output matched to their physiological responses during racing and training 11,12 . Although increases in fixed power output should be associated to greater muscle activation and pedal force application and/or to greater pedal force effectiveness, power output defined from intensity-based methods should be used to assess cyclists' strategies to accommodate changes in power output for a given exercise effort.…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, quase 2000 atletas competem nesta que é considerada uma das mais importantes provas da modalidade, já que é classi catória para a etapa do Havaí 6 . Com a popularização do triátlon "Ironman" e o crescente número de competidores nas diferentes etapas do circuito mundial, o nível pro ssional dos atletas aumentou ao longo dos anos 1,[7][8][9] . Associado a isso, novos equipamentos foram desenvolvidos ("aerobars", quadros de carbono e potenciômetros) e novas metodologias de treinamento têm sido propostas (inclusão do treinamento intervalado de alta intensidade, do treinamento de força e/ ou potência e a utilização de estratégias como o "taper") os quais vem contribuindo para a melhora do desempenho esportivo 2,[5][6][7][8][9] .…”
unclassified